2020
DOI: 10.5603/fhc.a2020.0011
|View full text |Cite
|
Sign up to set email alerts
|

Bisdemethoxycurcumin exerts a cell-protective effect via JAK2/STAT3 signaling in a rotenone-induced Parkinson’s disease model in vitro

Abstract: Introduction. Oxidative stress and cell apoptosis have both been suggested to be closely associated with the pathogenesis of Parkinson's disease (PD). Previously, bisdemethoxycurcumin (BDMC) has been shown to exhibit several desirable characteristics as a candidate neuroprotective agent, including antioxidant and anti-inflammatory activities in the nervous system. However, whether BDMC can exert cell-protective roles in an in vitro model of PD remains unknown. Material and methods. SH-SY5Y cells were pretreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Western blot analysis was conducted as described in previous studies. After the sample loading buffer was added, the tissue lysates were heated at 95 °C for 15 min and subjected to 10% SDS–PAGE, following an electroblot onto PVDF membranes. Then, membranes were blocked with 5% BSA diluted in Tris–HCl saline buffer for 1 h, following an incubation with the following primary antibodies: rabbit anti- nNOS (1:1000, ab76067, Abcam) or mouse anti-β-actin (1:1000; ab8226, Abcam) overnight at 4 °C.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Western blot analysis was conducted as described in previous studies. After the sample loading buffer was added, the tissue lysates were heated at 95 °C for 15 min and subjected to 10% SDS–PAGE, following an electroblot onto PVDF membranes. Then, membranes were blocked with 5% BSA diluted in Tris–HCl saline buffer for 1 h, following an incubation with the following primary antibodies: rabbit anti- nNOS (1:1000, ab76067, Abcam) or mouse anti-β-actin (1:1000; ab8226, Abcam) overnight at 4 °C.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Interestingly, another anti-diabetic drug MCC-555 reported to sensitize insulin signalling, can aid in the proper management of blood glucose levels, and amend inflammatory responses during SARS-CoV-2 infections 60,61 . Bisdemethoxycurcumin, a naturally occurring curcumin analogue, and Icilin, an activator of Transient Receptor Potential Melastatin–8 (TRPM8), are reported to possess anti-inflammatory properties and may also attenuate systemic inflammation or lung injury 62,63 . The inhibitory potential of the identified compounds and their reported clinical and pharmacological profile indicates that repurposing these drugs as monotherapy or combination therapy, should substantially speedup the drug development process against COVID-19 (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we employed the JAK2/STAT3 pathway inhibitor SC99 for the joint experiments. He et al have discovered a protective influence in a rotenone-induced PD model via enhancing the JAK2/STAT3 pathway (He et al, 2020). Wang et al have also shown that AS-IV can activate the JAK2/STAT3 pathway to stimulate angiogenesis, thereby playing a role in the clinical treatment of ischemic diseases (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…JAK2/STAT3 pathway is implicated in the neuroprotective effect of linagliptin on behavior disorders in mice (Elbaz et al, 2018). Bisdemethoxycurcumin is reported to play a protective role in a rotenone-induced PD model via the JAK2/STAT3 signaling pathway (He et al, 2020). However, whether AS-IV can prevent the injury of 6-OHDA-treated SH-SY5Y cells via regulating the JAK2/STAT3 pathway remains unclear.…”
Section: Introductionmentioning
confidence: 99%